Sorgo forrageiro implantado com diferentes arranjos populacionais manejado sob pastoreio contínuo - Rodrigues, Leonel da Silva (2016)
Objective was to evaluate the effects of different population arrangements in forage sorghum grazing on forage production, morphogenesis, pasture structure, performance, and animal behavior. They were used 36 crossed heifers between Charolais and Nellore, with initial age of 15 months and 262 kg of body weight (BW). The experimental period lasted 84 days, divided into periods of 28 days. The animals received daily supplementation to the level of 1% of body weight. Treatments consisted of a combination of spacings of 22 or 44 cm in planting spacing with two densities of seeds per hectare, 12 or 24 kg, resulting in arrangements population E44D12; E44D24; E22D12; E22D24. The grazing method was continuous with variable number of regulators animals. The forage mass and the mass of leaf blades did not differ between population arrangements, with average values of 1279.11 and 232.99 kg DM / ha. Similarly the stocking rate, dry matter accumulation rate and weight gain per area, with average values of 1172.32 kg LW / ha, 58.47 kg DM / ha / day and 303.31 kg PV / ha, in that order. The performance and development of the animals were not affected by population arrangements grassland, with weight gain and average final weight between treatments of 0.891 kg / day and 330.36 kg of PV. The relation weight:height among the population arrangements was 2.67 kg / cm, indicating that cross heifers between Charolais and Nellore with 18 months of age have fat thickness and appropriate weight for slaughter. Productive parameters of pasture and animal performance were influenced by evaluation periods. The different population arrangements change the behavioral patterns of animals, E44D24 and E22D12 treatments increase the grazing time. The E44D24 treatment decreases the bit rate when compared to E22D24. The lower density of plants per square meter causes the increase in the number of feeding stations / minute and the displacement rate of the animals. The spacing between rows 22cm promote a larger number of bits/food station. The use of higher density of seeds and larger spacing between lines increases the density of leaf blades in the lower and upper stratum of the pasture, respectively. The E44D12 and E22D24 treatments have higher amounts of stems in the upper stratum of the pasture (over 60 cm). Morphogenic variables were not significantly influenced by the different arrangements of plants used and the evaluation periods, being obtained elongation rate and leaf senescence of 1.43 and 1.11 cm/day/tiller, respectively, leaf appearance rate and leaf appearance interval of 0.28 leaves/day/tiller and 3.81 days phillochron and leaf life span of 72.99 and 351.68 degree day, in that order. Have the structural characteristics of pasture were influenced by evaluation periods, reflecting the forage production decline with advancing the use of the pasture cycle. The first to the third evaluation period was verified a reduction of 65.53% in the number of sheets in elongation and 47.79% in the number of living leaves.